Krisis Nilai Demokrasi atas Gugatan Sistem Pemilu Proporsional Terbuka ke Mahkamah Konstitusi oleh Elemen Masyarakat - Maulidi Maulidi; Zamroni Ishaq (JOSH: Journal of Sharia, 2023)
Democracy is government by the people. It is a system that is founded on the principle of people's sovereignty, with two main values attached to it, namely: freedom and equality. Freedom here automatically means freedom to be responsible and to move within the boundaries of the constitution, law and ethics. The electoral system is currently being widely discussed because there are requests from elements of society who are suing the open proportional electoral system to a closed proportional with the judicial review of Law Number 7 of 2017 concerning Elections filed on November 14, 2022. The lawsuit is registered with number 114/PPU/XX /2022 sues a number of articles in the Election Law which rely on Article 168 paragraph (2) concerning the open list proportional legislative election system. The petitioners argue that an open proportional electoral system is contrary to the constitution. This is because Article 18 paragraph (3) and Article 19 of the 1945 Constitution state that members of the DPR and DPRD are elected in elections, where the participants are political parties. On June 15, 2023 the Constitutional Court rejected the applicant's application in its entirety.